2015
DOI: 10.1515/jpem-2014-0446
|View full text |Cite
|
Sign up to set email alerts
|

Rickets and vitamin D deficiency in Alaska native children

Abstract: Background Rickets and vitamin D deficiency appeared to increase in Alaskan children, starting in the 1990s. We evaluated the epidemiology of rickets and vitamin D deficiency in Alaska Native (AN) children in 2001-2010. Methods We analyzed 2001-2010 visits with rickets or vitamin D deficiency diagnosis for AN and American Indian children and the general U.S. population aged <10 years. We conducted a case-control study of AN rickets/vitamin D deficient cases and age- and region-matched controls. Results AN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
1
34
0
1
Order By: Relevance
“…We developed a particular interest in the role that changing diets of childbearing women may have on vitamin D deficiency and rickets in children after a recent study reported a high incidence of rickets in Alaska Native children relative to other populations (4) , following a report of rickets diagnoses in Alaska in the 1990’s (5) . Of the confirmed rickets diagnoses, 63% were in children under 1 year of age (4) , suggesting the importance of maternal vitamin D status. Previous dietary evaluations in Alaska Native people showed higher vitamin D intake in Alaska Native people eating a traditional subsistence diet (2; 3; 6; 7) , mirroring trends found in the Canadian Arctic (8; 9; 10) and Greenland (11; 12; 13) .…”
Section: Introductionmentioning
confidence: 99%
“…We developed a particular interest in the role that changing diets of childbearing women may have on vitamin D deficiency and rickets in children after a recent study reported a high incidence of rickets in Alaska Native children relative to other populations (4) , following a report of rickets diagnoses in Alaska in the 1990’s (5) . Of the confirmed rickets diagnoses, 63% were in children under 1 year of age (4) , suggesting the importance of maternal vitamin D status. Previous dietary evaluations in Alaska Native people showed higher vitamin D intake in Alaska Native people eating a traditional subsistence diet (2; 3; 6; 7) , mirroring trends found in the Canadian Arctic (8; 9; 10) and Greenland (11; 12; 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Singleton R in his article on rickets and vitamin D deficiency in Alaska native children concluded that rickets incidence increased with latitude and rickets/vitamin D deficiency cases are more likely to have malnutrition (OR 38.1; 95% CI 4.9-294). 6 No such study has been conducted any where in the world on the tea garden community in spite of possible evidence of higher incidence of rickets in this community due to altitude, malnutrition, and low socioeconomic status. On extensive literature search, only one other study conducted in Bangladesh has tried to identify incidence of skeletal deformity in rickets.…”
Section: Discussionmentioning
confidence: 99%
“…In some Native Arctic populations, large quantities of wild caught foods, including salmon and other fish, contribute significantly to the diet (Ballew et al, 2006). Numerous researchers have reported improved vitamin D status and health outcomes in Native Alaskan and other Arctic populations consuming a diet rich in traditional foods (Andersen et al, 2013;Bersamin et al, 2007;Johnson et al, 2009; Sheehy et al, 2014;Singleton et al, 2015). However, the conclusions about specific nutrient and health outcomes rest on the quality and completeness of food composition data, which are lacking .…”
Section: Nutritional Significancementioning
confidence: 99%
“…Suboptimal vitamin D status has been documented in a variety of Arctic and sub-Arctic populations, including Alaskan and Canadian Northwest Native Americans (Frost and Hill, 2008;Lebrun et al, 1993;Sharma et al, 2011;Singleton et al, 2015;Weiler et al, 2007). There has been a trend toward westernization of the diet of Native populations (Ballew et al, 2006;Johnson et al, 2009;Murphy et al, 1995;Nobmann et al, 2005), although greater consumption of traditional foods in North American Arctic and sub-Arctic populations has been associated with better vitamin D status (Andersen et al, 2013;Bersamin et al, 2007;Luick et al, 2014;Mansuri et al, 2016;Mohatt et al, 2007;Ryman et al, 2015;Sheehy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%